2004
DOI: 10.1038/sj.jp.7211189
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Ramadan Fasting and Neonatal Health

Abstract: This retrospective cohort study sought to determine the effects of maternal Ramadan fasting during pregnancy on neonatal birth weight as an important aspect of fetal health. It was carried out among healthy women who were admitted for their neonate delivery at two medical centers in Tehran from January to September 2000. Neonates of 284 mothers with a history of Ramadan fasting during pregnancy were compared with neonates of 255 mothers who did not have a history of fasting during their pregnancies. On univari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 9 publications
6
37
1
1
Order By: Relevance
“…Our results, showing that pregnant women who are fasting are heavier and have a higher parity, have also been reported in studies conducted in Iran and Singapore respectively [15, 16]. The relationships we observed between higher parity and lower maternal age being related to fasting were however not observed in another Iranian maternal cohort [17].…”
Section: Discussionsupporting
confidence: 88%
“…Our results, showing that pregnant women who are fasting are heavier and have a higher parity, have also been reported in studies conducted in Iran and Singapore respectively [15, 16]. The relationships we observed between higher parity and lower maternal age being related to fasting were however not observed in another Iranian maternal cohort [17].…”
Section: Discussionsupporting
confidence: 88%
“…A significant fall in glucose, insulin, lactate and carnitine and a rise in triglycerides and hydroxybutyrate was reported at the end of the fasting day in pregnant women [116] . In another reports the LDL/HDL ratio was decreased and the outcome of pregnancy was comparable to those who did not fast [117,118] . The outcome of pregnancy in Gambian women who fasted during Ramadan was unsatisfactory; however, no control group was evaluated [119] .…”
Section: Pregnancy and Lactationmentioning
confidence: 98%
“…A MEDLINE search of articles containing the word 'Ramadan' or a combination of 'fasting' plus either 'Muslim' or 'Islam' found that researchers have examined the effect of fasting during Ramadan on diabetes (Salti et al 2004, Sari et al 2004, breast milk composition (Rakicioglu et al 2006, Rashid 2007, cholesterol levels (Adlouni et al 1998, Qujeq et al 2002, seizure activity (Gomceli et al 2008), incidence of acute cardiac events (Al suwaidi et al 2004a), incidence of hospitalisation for congestive heart failure (Al Suwaidi et al 2004b), frequency of emergency department visits (Topacoglu et al 2005) and neonatal birth weight (Kavehmanesh and Abolghasemi 2004). Several studies have noted inadequate hydration (Schmahl andMetzler 1991, Leiper andMolla 2003); variations in nutritional intake (Gharbi et al 2003, Lamine et al 2006, Reilly and Waterhouse 2007; challenges with medication, administration and adherence (Aadil et al 2004, Habib et al 2008; and inadequacy of sleep (Roky et al 2003) during Ramadan.…”
Section: Introductionmentioning
confidence: 99%